A eficácia da política monetária dos BRICS medida por meio do estudo de sensibilidade das taxas de juros no período de 2000 a 2014 - Machado, Maurício Morsbach (2015)
The main issue studied in this work concerns the measurements required in the application of interest rates, due to their sensitivity, front to output and inflation gaps. The results show significant differences in the presence of shocks, both with the expected effects in the control of output and inflation, as well as amplifying these effects, acting in a manner contrary to the usually expected. To obtain these results were estimated neutral interest rate of BRICS and a VAR model defining the determinants of the rate of interest for each of these countries. These results were compared to actual rates in order to identify the goals to be pursued. After it we used the function impulse-response to measure the effects of a shock of interest in output and inflation gaps showing how the sensitivity of the interest rate affects the control of inflation rates and the promotion of economic growth and that high dosages are required when the sensitivity of the interest rate is low and reduced dosages when this sensitivity is high